Embedding indigenous learning outcomes in a tourism curriculum: The case of Confederation College, Canada. (June 2020) - Joppe, Marion; Shen, Ye (Sandy); Veltri, Giannina
Abstract: Although hospitality and tourism students in business programs are taught to develop and market product that meets the needs of various demand segments by playing on the "authentic" cultural and heritage elements of destinations, they are rarely exposed to underlying justice and ethics concerns, especially as they pertain to Indigenous populations. In a settler colonial country such as Canada, it is particularly imperative that these topics are addressed and that students learn about Indigenous ways of knowing, being and doing to ensure that they have the necessary cultural competencies to build a respectful relationship with Indigenous populations, wherever their career may take them. The goal of this research is to provide a deeper understanding of the process of developing and embedding Indigenous Learning Outcomes in a tourism business program and to suggest underlying principles for designing a more inclusive community engagement process. The case is that of the Tourism – Travel and Eco-Adventure program at Confederation College in Thunder Bay, Ontario, Canada. The College has been recognized as a leader in Indigenous education and that is in the process of implementing a comprehensive vision for the transformation of the institution informed by Indigenous community engagement and its learning community.